Development Strategy and Digital Leadershipin Encouraging Digital Competence for Optimizing Public Services - Slamet Teguh; I Kadek Wisnu Ciptadi (Proceeding of The International Conference on Business and Economics, 2026)
This study examines the role of human resource development strategies and digital leadership in enhancing the digital competence of civil servants, which in turn drives the optimization of public services. Digital transformation is imperative in the public sector to improve efficiency, transparency, and accountability in public services. However, the success of this transformation depends heavily on the readiness of human resources and effective digital leadership. This study analyzes the influence of development strategies on civil servant digital competence, as well as the influence of digital leadership on digital competence and public services. This study uses a quantitative approach with data analysis using SmartPLS. The results indicate that human resource development strategies and digital leadership have a significant influence on improving civil servant digital competence and ultimately optimizing public services. This research makes an important contribution to understanding the relationship between these three variables in the context of Indonesian government bureaucracy and the importance of human resource development and digital leadership in the era of digital transformation.